2010
DOI: 10.1002/ijc.25072
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of branched chain amino acid metabolism in tumors with hyperpolarized 13C ketoisocaproate

Abstract: Powerful analytical tools are vital for characterizing the complex molecular changes underlying oncogenesis and cancer treatment. This is particularly true, if information is to be collected in vivo by noninvasive approaches. In the recent past, hyperpolarized 13 C magnetic resonance (MR) spectroscopy has been employed to quickly collect detailed spectral information on the chemical fate of tracer molecules in different tissues at high sensitivity. Here, we report a preclinical study showing that a-ketoisocap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 36 publications
(170 reference statements)
1
80
0
Order By: Relevance
“…Increased glutamate concentration has also been reported by previous studies as a common phenomenon in tumors [41]. Furthermore, Magnus Karlsson and coworkers have reported that increased glutamate pools in tumors leads to increased leucine formation, a consistent result reflected in this study [42]. The blockade of glutamate receptors has been proposed as a promising novel therapy for treating melanoma [43].…”
Section: Discussionsupporting
confidence: 89%
“…Increased glutamate concentration has also been reported by previous studies as a common phenomenon in tumors [41]. Furthermore, Magnus Karlsson and coworkers have reported that increased glutamate pools in tumors leads to increased leucine formation, a consistent result reflected in this study [42]. The blockade of glutamate receptors has been proposed as a promising novel therapy for treating melanoma [43].…”
Section: Discussionsupporting
confidence: 89%
“…This 13 CO 2 rapidly In many cases, higher unpublished levels of polarization have been achieved with these molecules, and in some cases a gadolinium chelate has also been added to improve polarization (47). Results obtained at higher polarization field show further increase in polarization levels (33,43). Abbreviations: ALT, alanine transaminase; BCAT, branched-chain amino acid transferase; GLUT5, glucose transporter; LDH, lactate dehydrogenase; PDH, pyruvate dehydrogenase; PPP, pentose phosphate pathway.…”
Section: [1-13 C]pyruvatementioning
confidence: 97%
“…Importantly, a large part of the pulse sequence development has been performed at 3 T on clinical systems, which is likely to speed up their availability in the clinic. Several studies have used a simple spectroscopic imaging sequence (19,26,40,43), with phase-encoding gradients in two or three directions. The sequence is widely available in a clinical setting, has relatively lowgradient amplitude requirements, and detects all the resonances simultaneously with high spectral quality.…”
Section: Imaging Hyperpolarized Nucleimentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of ALT has been detected previously using hyperpolarized [1][2][3][4][5][6][7][8][9][10][11][12][13] C]pyruvate in tumors, skeletal muscle, and in liver, where the formation of [1-13 C]alanine has been detected (2,6). ALT activity has also been detected in heart and liver from the formation of [1][2][3][4][5][6][7][8][9][10][11][12][13] C]pyruvate following the administration of hyperpolarized [1-13 C]alanine (12). Glutamate is an important nitrogen source and is involved in nitrogen transport within the body and in the central nervous system.…”
mentioning
confidence: 99%